Calorie Restriction Attenuates Terminal Differentiation of Immune Cells - White, Matthew J.; Beaver, Charlotte M.; Goodier, Martin R.; Bottomley, Christian; Nielsen, Carolyn M.; Wolf, Asia-Sophia F. M.; Boldrin, Luisa; Whitmore, Charlotte; Morgan, Jennifer; Pearce, Daniel J.; Riley, Eleanor M. (Frontiers in Immunology, 2017)
Immune senescence is a natural consequence of ageing and may contribute to frailty and loss of homeostasis in later life. Calorie restriction increases healthy life-span in C57BL/6J (but not DBA/2J) mice but whether this is related to preservation of immune function, and how it interacts with ageing, is unclear. We compared phenotypic and functional characteristics of Natural Killer (NK) cells and T cells, across the lifespan, of calorie-restricted and control C57BL/6 and DBA/2 mice. Calorie restriction preserves a naïve T cell phenotype and an immature NK cell phenotype as mice age. The splenic T cell populations of calorie restricted mice had higher proportions of CD11a-CD44lo cells, lower expression of TRAIL, KLRG1 and CXCR3 and higher expression of CD127, compared to control mice. Similarly, splenic NK cells from calorie restricted mice had higher proportions of less differentiated CD11b-CD27+ cells and correspondingly lower proportions of highly differentiated CD11b+CD27-NK cells. Within each of these subsets, cells from calorie restricted mice had higher expression of CD127, CD25, TRAIL, NKG2A/C/E, and CXCR3 and lower expression of KLRG1 and Ly49 receptors compared to controls. The effects of calorie restriction on lymphoid cell populations in lung, liver and lymph nodes were identical to those seen in the spleen, indicating that this is a system-wide effect. The impact of calorie restriction on NK cell and T cell maturation is much more profound than the effect of ageing and, indeed, calorie restriction attenuates these age-associated changes. Importantly, the effects of calorie restriction on lymphocyte maturation were more marked in C57BL/6 than in DBA/2J mice indicating that delayed lymphocyte maturation correlates with extended lifespan. These findings have implications for understanding the interaction between nutritional status, immunity and healthy lifespan in ageing populations.